ϖ-Interpolative Ciric-Reich-Rus-Type Contactions in m-metric space - Umair, Muhammad; Hassan, Ahmad; Hassan, Ali; Hussain, Abid; Faiz, Habiba; Maqbool, Sana Naz; Jamil, Muahmmad (International Journal of Advanced Engineering Research and Science, 2023)
In this paper, using the concept of ϖ-admissibility, we prove some fixed -point results for interpolate Ciric-Reich-Rus-type contraction mappings. We also present some consequences and a useful example.